A comparison of the minimum data sets for primary shoulder arthroplasty between national shoulder arthroplasty registries. Is international harmonization feasible?. (July 2019) - Aveledo, Ricardo; Holland, Phillip; Thomas, Michael; Ashton, Fiona; Rangan, Amar
The aims of this study were to identify the common components of the Minimum Data Set (MDS) of current national shoulder arthroplasty registries that could be pooled for analysis; and to determine whether further harmonisation of data collection across these registries would be feasible. Copies of primary shoulder arthroplasty MDS forms, annual reports, and other publications from national shoulder arthroplasty registries were identified using internet search engines up to November 2016. Data relating to local or regional registries was excluded. There were nine national shoulder arthroplasty registries reporting a total of 97, 388 primary shoulder replacements. All minimum data sets included patient identifiers, date of surgery, implant identification, laterality of surgery, indication and mode of implant fixation. At least 6 registries had common options within the categories of indication, implant fixation and previous operations. Most discrepancies were seen in categories for additional interventions, outcome measures, and intra-operative complications. As numbers within individual registries are relatively small, international collaboration would harness the global strength of knowledge and experience in shoulder replacement. Several similarities were identified between the current national registries that could become unified with only minor changes by a few registries, highlighting the potential feasibility of MDS harmonisat.